Investigations into the role of Cten signalling in colorectal cancer - Asiri, Abdulaziz (2018)
C-terminal tensin-like (Cten, also known as Tensin4) is the member of the tensin gene family. Cten functions as an oncogene in a variety of cancer types and its expression is commonly associated with poor prognosis and metastasis in colorectal cancer (CRC). Although several studies have shown that Cten has a critical role in the regulation of cell motility and invasion in different tumour tissues, the underlying signalling mechanisms have not been fully elucidated. This thesis investigated the biological activity of Cten in four different ways in order to further elucidate the mechanisms of Cten signalling in CRC cells.